Polybrominated diphenyl ethers (PBDEs) and hydroxylated PBDE metabolites (OH-PBDEs): A six-year temporal trend in Northern California pregnant women. (March 2018) - Parry, Emily; Zota, Ami R.; Park, June-Soo; Woodruff, Tracey J.
Abstract: Polybrominated diphenyl ethers (PBDEs) are brominated flame retardants. Technical mixtures PentaBDE and OctaBDE were phased out in 2004 through voluntary and regulatory actions with DecaBDE remaining in limited use until 2013. Biomonitoring studies have shown widespread presence of PBDEs in the US and worldwide population. While some studies suggest that human serum concentrations are declining over time, it is unclear whether this trend will continue. Our objective was to examine temporal trends of PentaBDEs and their hydroxylated metabolites (OH-PBDEs) between 2008 and 2014 in populations of ethnically diverse, pregnant women residing in Northern California (n = 111). Serum samples were collected and analyzed by high resolution mass spectrometry for five PentaBDE congeners and two OH-PBDEs. We found widespread exposures in participants from all three time points (2008/09, 2011/12, 2014). Temporal patterns varied substantially by congener. BDE-47, -99 and the OH-PBDEs decreased between 2008/09-2011/12 but plateaued between 2011/12-2014. In contrast, BDE-100 decreased across all years, BDE-153 decreased in the latter years, and BDE-28 decreased initially and then increased. These findings indicate that while policies to remove PBDEs from the marketplace have successfully lead to declines in exposures to some PBDE congeners, human exposures to these legacy pollutants could plateau and remain ubiquitous in human populations. Highlights: We measured PBDEs and OH-PBDEs in a demographically consistent population of pregnant women over six years. Between 2008/09 and 2011/12, ∑PBDE5 concentrations decreased 45%, but plateaued between 2011/12 and 2014. BDE-47 was found in 100% of pregnant women in all years studied. The BDE-153 concentration decreased more between 2011/12 and 2014 than between the prior cohorts.